Bertha and bear - Sharp, Christine (university of queensland press Queensland, 2020)
A gorgeous and heartfelt picture book about a little bee searching for a new home and finding friendship in unlikely places. There's a storm brewing and the hive must find a new home. With clouds filling the sky and thunder growling, Bertha bravely rises to the occasion ... until she meets BEAR, that is! Bertha and Bear is a book about friendship, finding your place and the courage of one brave little bee